1997
DOI: 10.1128/aem.63.2.474-481.1997
|View full text |Cite
|
Sign up to set email alerts
|

Stable-Isotope Analysis of a Combined Nitrification-Denitrification Sustained by Thermophilic Methanotrophs under Low-Oxygen Conditions

Abstract: To simulate growth conditions experienced by microbiota at O 2-limited interfaces of organic matter in compost, an experimental system capable of maintaining dual limitations of oxygen and carbon for extended periods, i.e., a pO 2-auxostat, has been used. 15 N tracer studies on thermophilic (53؇C) decomposition processes occurring in manure-straw aggregates showed the emission of dinitrogen gas from the reactor as a result of simultaneous nitrification and denitrification at low pO 2 values (0.1 to 2.0%, vol/v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…In addition, the incorporation of 13 C-label into phospholipid-derived fatty acids (PLFA) was determined to study the bacterial populations involved in these processes. Both ourselves and others have recently shown that this approach enables the direct linking of microbial populations to speci¢c processes in environmental samples [1,11,12] and in model communities [2,13]. Our results suggest that propionate was directly taken up from the porewater without the formation of acetate as an intermediate, and that acetate and propionate were predominantly consumed by di¡erent populations or groups of bacteria.…”
Section: Introductionmentioning
confidence: 54%
See 4 more Smart Citations
“…In addition, the incorporation of 13 C-label into phospholipid-derived fatty acids (PLFA) was determined to study the bacterial populations involved in these processes. Both ourselves and others have recently shown that this approach enables the direct linking of microbial populations to speci¢c processes in environmental samples [1,11,12] and in model communities [2,13]. Our results suggest that propionate was directly taken up from the porewater without the formation of acetate as an intermediate, and that acetate and propionate were predominantly consumed by di¡erent populations or groups of bacteria.…”
Section: Introductionmentioning
confidence: 54%
“…The limit of detectable increase in N 13 C is about 1^2x, which is mainly the result of natural variation in N 13 C ratios of the unlabelled control incubations and to a lesser extent of analytical methods (0.3x accuracy). Incorporation of label was very speci¢c, as increases in N 13 C ratios (vN 13 C, equivalent to speci¢c incorporation = amount of 13 C/amount of PLFA) were highly variable between bacterial PLFA and showed a range of 10 for 13 C-acetate incorporation and s 100 for 13 C-propionate incorporation (Figs. 3A and 4A).…”
Section: Acetate and Propionate Incorporation Into Plfamentioning
confidence: 99%
See 3 more Smart Citations